THU0224 Knee Effusion is A Risk Factor for Prevalence and Progression of Bone Marrow Lesions: A Population-Based Study. (10th June 2014) - Cibere, J.; Kopec, J.A.; Wong, H.; Singer, J.; Esdaile, J.M.; Nicolaou, S.; Guermazi, A.
Abstract : Background: Bone marrow lesions (BML) occur commonly in knee osteoarthritis (OA) and may be a target for intervention in randomized controlled trials. The potential benefit of therapeutic interventions in OA is likely enhanced if aimed at early stage disease. We have previously shown that knee effusion is associated with cartilage damage in early knee OA, but it is unknown whether knee effusion is associated with BML in early disease. Objectives: To evaluate whether knee effusion on physical examination is associated with prevalent BML and with progression of BML over 3 years. Methods: Population-based longitudinal cohort study of subjects, age 40-79, with knee pain. Subjects were evaluated at baseline and follow-up (mean 3.2 years) using standardized knee examination, fixed-flexion knee radiographs and MRI (1.5T). Only subjects with Kellgren-Lawrence (KL) radiographic grade 0-2 were included in this analysis. Knee effusion on examination was scored as present or absent. BML was scored on MRI on a 0-3 scale at 6 joint sites and the maximum score at any site was used in the analysis. Progression of BML was defined as worsening by ≥1 grade in those with BML 0-2 at baseline. Due to small numbers incidence and progression of BML could not be evaluated separately. MRI was read semi-quantitatively for cartilage damage (0-4 scale). Logistic regression analysis was used to evaluate the association of baseline knee effusion with BML prevalence and with BML progression. Analyses were adjusted for age, sex and body mass index. Results: At baseline (n=199), mean age was 56 years, 50% were female and 16% had a knee effusion. KL grade 0, 1 and 2 was present in 50%, 28% and 22%, respectively. Cartilage damage on MRI was seen in 88%. BML was present in 79/199 subjects (40%). Of those with BML, 23/79 (29.1%) had effusion, compared to those without BML, where 8/120 (6.7%) had effusions. Knee effusion on examination was significantly associated with prevalent BML (OR 5.41, 95% CI 2.20-13.28). In this model, age was also significant with the risk of BML increased in those aged ≥50 years, compared to those aged 40-49 (OR 3.33, 95% CI 1.65-6.70). At follow-up (n=124), progression of BML was seen in 25/124 subjects (20.2%). Of these, 9/72 (12.5%) progressed from BML 0 to higher grades, while 16/52 (30.8%) progressed from BML 1 or 2 to higher grades. Baseline knee effusion was associated with a significant risk of progression of BML at 3 years (OR 3.02, 95% CI 1.01-9.01). Conclusions: In this population-based cohort of early knee OA, the risk of prevalent BML and the risk of BML progression were both significantly increased in those with effusion compared to those without effusion on knee examination at baseline. Whether effusion is related to BML progression through common inflammatory signals or through other mechanisms requires further study. Evaluation for knee effusion may be a useful and inexpensive clinical test for potential identification of subjects with BML in clinical trials. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4840